Sociālpedagoģiskā darbība sociālo prasmju apguvei internātpamatskolas audzēkņiem. - Grundīza, Sandra (Latvijas Universitāte, 2006)
Sociālās prasmes un iemaņas ir svarīgs faktors indivīda pilnvērtīgai eksistēšanai sabiedrībā. Bērna sākotnējo sociālo prasmju apguvē svarīga loma ir ģimenei. Skolā notiek organizēts socializācijas process, tas ir nepārtraukts darbs, kurā iesaistās pedagogi un sociālais pedagogs. Autore darbā analizēja pedagoģisko un psiholoģisko literatūru par sociālām prasmēm. Pētījuma rezultātā tika noskaidroti sociālo prasmju apguves riska faktori internātpamatskolas audzēkņu ģimenēs. Darba autore izstrādāja un realizēja sociālpedagoģisko darbības programmu skolēnu sociālo prasmju apguvei internātpamatskolas sākumposmā.

Nowadays the society demands a lot of social skills and abilities from our students to exist and communicate with others successfully. Family takes the most important part in child’s social skill acquirement at the beginning stage of their development. The socialization process at school is in progress all the time; it is a continuous work, in which all the teaching staff is involved and should take and active part in it. The current research includes the analysis of pedagogical and psychological literature about social skills. The results of the research show that the social skill acquirement risk factors of students learning at grammar boarding school can be found in their families. The author of the current paper worked out and realized a social – pedagogical program to acquire social skills at grammar boarding school in the beginning stage
Social pedagogical work for the acquisition of social skills of the boarding primary school learners.
Keywords: Sociālais pedagogs [fakultāte]